Seasonal change in trace element concentrations of Paracentrotus lividus: Its use as a bioindicator. (May 2020) - El Idrissi, O.; Marengo, M.; Aiello, A.; Gobert, S.; Pasqualini, V.; Ternengo, S.
Highlights: Importance physiological factors have been identified. Gonadosomatic index is the variable most closely related to temporal variations. Trace elements contamination is lower during the summer season. The use of gonads should be avoided during the spawning period (autumn/winter). Abstract: An assessment of classical and emerging trace element contamination was conducted on gonads of the sea urchin Paracentrotus lividus (Lamarck, 1819), in Corsica (Western Mediterranean). The aim of this study was to evaluate the contamination levels at different sites by following the seasonal variation of 22 trace elements. The sea urchins analyzed were taken in 2017 from reference and more impacted sites in four Corsican areas. The results obtained shown the importance of biotic factors such as gender, reproduction and the way of life. Variations have been highlighted with lower trace element concentrations during the summer season. This is mainly due to a dilution phenomenon resulting from gametogenesis. The pollution index (TEPI) was determined and highlighted differences in contamination levels at the various sites. This work could provide additional support for other tools for the diagnosis and monitoring of coastal water quality. It provides useful new data to enable managers to act at the source and reduce degradation in order to improve the ecological quality of marine waters.